Status and outlook of the neutron time-of-flight facility n_TOF at CERN - Gunsing, F. (2007)
The neutron time-of-flight facility n_TOF at CERN, fully operational since 2002, combines a high instantaneous neutron flux with high energy resolution. The wide energy range and the high neutron flux per time-of-flight burst result in a much enhanced signal to background ratio for neutron capture of radioactive isotopes and makes this facility well suited for the measurement of high quality neutron-induced reaction cross-sections.